Adventitial Cells and Perictyes Support Chondrogenesis Through Different Mechanisms in 3-Dimensional Cultures With or Without Nanoscaffolds - Zhang, Shu; Ba, Kai; Wu, Ling; Lee, Siyong; Peault, Bruno; Petrigliano, Frank A; McAllister, David R; Adams, John S; Evseenko, Denis; Lin, Yunfeng (Journal of biomedical nanotechnology, 2015)
In previous studies, mesenchymal stromal cells (MSCs) derived from bone marrow and fat tissues were shown to increase proliferation and matrix production of chondrocytes (CH) in co-culture. The aim of this study was to investigate the roles of pericytes (CD31(neg)CD45(neg)CD146+CD34(neg)) and adventitial cells (CD31(neg)CD45(neg)CD146(neg)CD34+) sub-populations of MSCs in supporting proliferation and matrix deposition of CH. The MSCs were derived from synovial membrane and attaching fat tissue. Then, the pericytes and adventitial cells were sorted from total MSCs and co-cultured with articular CH respectively. In pellet co-culture model, the pericytes showed more prominent effects on glycosaminoglycans (GAGs) production and Collagen II synthesis than the adventitial cells which had stronger effects on promoting CH proliferation. In addition, quantitative polymerase chain reaction (qPCR) was performed to examine the expression of a group of secreted growth factors and co-culture performed on electrospun scaffolds based on Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (P3HB4HB), to verify the trophic effects of different MSC sub-populations in 3-Dimensional (3D) environment. In conclusion, it was found that the pericytes and adventitial cells support CH in different ways; the adventitial cells more supporting the proliferation of CH, while pericytes are better in stimulating GAGs and collagen production of CH.